2022
DOI: 10.1038/s41598-022-14820-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of novel as-cast Ti-Mo-Nb alloys for biomedical applications

Abstract: Ti and its alloys are the most used metallic biomaterials devices due to their excellent combination of chemical and mechanical properties, biocompatibility, and non-toxicity to the human body. However, the current alloys available still have several issues, such as cytotoxicity of Al and V and high elastic modulus values, compared to human bone. β-type alloys, compared to α-type and (α + β)-type Ti alloys, have lower elastic modulus and higher mechanical strength. Then, new biomedical β-type alloys are being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Notably, this value is lower than that of the commercial shape-memory alloy TNTZ-O, 88.7 GPa. The reason behind that is the presence of the β-Ti phase, adding a percentage of Mo a presenting a β-Ti phase which reduces the mechanical properties [20,21]. Depending on modeling, a set of experimental parameters can be used to characterize the powder neutron diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, this value is lower than that of the commercial shape-memory alloy TNTZ-O, 88.7 GPa. The reason behind that is the presence of the β-Ti phase, adding a percentage of Mo a presenting a β-Ti phase which reduces the mechanical properties [20,21]. Depending on modeling, a set of experimental parameters can be used to characterize the powder neutron diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%
“…This was explained by the formation of the TiO passive layer limiting the release of ions from titanium alloys [ 21 ]. Cardoso et al also found that pure titanium alloys used in combination with molybdenum (Mo) and niobium (Nb) elements showed no cytotoxicity effect as the result of cpTi alone [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ti-30Nb-5Mo alloy was produced by arc-melting in an argon-controlled atmosphere and in a water-cooled copper crucible. The details of the cast and bulk properties of this alloy can be found in previous works [35][36][37]. After melting, the produced ingots were hot rolled to reach a thickness of 1 mm, and cut to obtain square samples measuring 10 × 10 mm 2 .…”
Section: Methodsmentioning
confidence: 99%